Silicate nanoparticles by bioleaching of glass and modification of the glass surface - Kulkarni, Sneha; Syed, Asad; Singh, Sanjay; Gaikwad, Anil; Patil, Kashinath; Vijayamohanan, K.; Ahmad, Absar; Ogale, Satishchandra (Journal of Non-Crystalline Solids, 2008)
Bioleaching is examined as a low temperature (50 degrees C) soft chemical approach to nanosynthesis and surface processing. We demonstrate that fungus based bioleaching of borosilicate glass enables synthesis of nearly monodispersed ultrafine (similar to 5 +/- 0.5 nm) silicate nanoparticles. Using various techniques such as X-ray diffraction, X-ray photoelectron spectroscopy and FTIR we compare the constitution and composition of the nanoparticles with that of the parent glass, and establish the basic similarities between the two. The bioleaching process is shown to enhance the non-bridging oxygen component and correspondingly influence the Si-O-Si network. The root mean square roughness of glass surface is seen to increase from 1.27 nm for bare glass to 2.52 nm for 15 h fungal processed case, this increase being equivalent to that for glass annealed at 500 degrees C. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Biomaterials; borosilicates; narroparticles

XPS and AFM investigations on silver-based photoimageable thick film systems - Umarji, Govind; Ketkar, Supriya; Hawaldar, Ranjit R.; Gosavi, Suresh W.; Patil, Kashinath; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Microelectronics International, 2008)
Purpose - The purpose of this paper is to ascertain chemical changes occurring at various stages involved in processing of silver-based photoimageable thick films; and to determine ensuing topographical features which other wise appeared to be hindered in 2D scanning electron microscopy. Design/methodology/approach - Surface sensitive techniques, viz. X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM) were used. Findings - Interfacial adhesion of silver film with substrate (Al(2)O(3)) was specifically looked into with respect to role played by photoimaging (before and after exposure to ultra-violet light). XPS results revealed occurrence of subtle chemical changes in terms of unsaturation to saturation in C-C bonding and also an interesting C-Al bonding which presumably improves mechanical adhesion of unfired film with the alumina substrate. AFM was carried out to examine the surface roughness, particle size, and microstructure of film which are very important from the standpoint of high-frequency applications. Originality/value - Surface sensitive techniques like XPS and AFM were exclusively used in order to characterize silver-based photoimageable thick films.
Keywords: microscopy; Silver; thick film circuits; X-rays

Surfactant tunable hierarchical nanostructures of CdIn2S4 and their photohydrogen production under solar light - Bhirud, Ashwini P.; Chaudhari, Nilima; Nikam, Latesh; Sonawane, Ravindra; Patil, Kashinath; Baeg, Jin-Ook; Kale, Bharat (International Journal of Hydrogen Energy, 2011)
The hierarchical nanostructures of CdIn2S4 were selectively prepared through hydrothermal process in the presence of different surfactants. Structural study demonstrated existence of cubic spinel structure and micro structural study shown a pretty marigold flower like morphology without any surfactant. The effect of surfactants on the morphology and microstructure of CdIn2S4 has been studied by using Polyvinyl pyrrolidone (PVP) and Cetyltrimethyl ammonium bromide (CTAB) as a surfactants. The CdIn2S4 bipyramids with length of 0.7-1 mu m have been obtained using PVP. Interestingly, the nanopetals (thin and transparent) of CdIn2S4 are self assembled into hollow spheres in the presence of CTAB. Considering the importance of these unique nanostructures, the growth mechanism has also been proposed. The optical properties demonstrated the band gap in the range of 2.12-2.29 eV which is well within the visible region. In this contest, photocatalytic activity for hydrogen production using the above nanostructures under visible light was also demonstrated. The prima-fascia observations shows that the bipyramidal CdIn2S4 exhibit excellent photocatalytic activity for hydrogen production (3238 mu molh(-1)) than other nanostructures. Being a nanostructured semiconductor chalcogenide with a good stability will also have potential applications in solar cells and LED. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Bipyramids; CdIn2S4; Hydrogen generation; hydrothermal; Self-assembled

Development of a novel method to grow mono-/few-layered MoS2 films and MoS2-graphene hybrid films for supercapacitor applications - Patil, Sagar; Harle, Arti S.; Sathaye, Shivaram; Patil, Kashinath (CrystEngComm, 2014)
The controlled synthesis of highly crystalline MoS2 atomic layers remains a challenge for practical applications of this emerging material. We demonstrate a facile method to synthesize crystalline mono-layered/few-layered MoS2 thin films at the liquid-liquid interface which can be suitably transferred to the substrates. The films are characterized by XRD for their crystal structure and by SEM and TEM for the morphology. MoS2 nanosheet-graphene nanosheet (MoS2-GNS) hybrid films have been developed by the application of layer-by-layer (LbL) techniques. Cyclic voltammetry and other electrochemical characterization techniques reveal that the hybrid film electrode shows a specific capacitance of 282 F g(-1) at a scan rate of 20 mV s(-1). The as-obtained hybrid electrode is robust and exhibits much improved cycle life (>1000), retaining over 93% of its initial capacitance as revealed by galvanostatic charge/discharge studies. The confirmation of better performance as a supercapacitor of the composite was studied by electrochemical impedance spectroscopy. These results indicate that the MoS2-GNS hybrid is a promising candidate for the electrode material in supercapacitor applications.

Facile room temperature methods for growing ultra thin films of graphene nanosheets, nanoparticulate tin oxide and preliminary assessment of graphene-tin oxide stacked layered composite structure for supercapacitor application - Patil, Sagar; Patil, Virendra; Sathaye, Shivaram; Patil, Kashinath (RSC Advances, 2014)
We report a novel, facile, single step process for growing highly uniform few layer graphene nanosheet (FLGNS) thin films over a micrometer scale, formed at the liquid-air interface. The process is further extended to form monolayer graphene nanosheets (GNS). The films are characterized by Raman spectroscopy, Atomic force microscopy (AFM) and X-ray photoelectron spectroscopy (XPS). The results indicate that very few chemical and/or physical defects are introduced during formation of films. Further, an innovative single step method to form tin oxide (SnO2) films at the liquid-air interface is presented. A special feature of the method is that entire process is completed at room temperature. The film can be suitably transferred to the desired substrates by Blodgett technique. Characterization by various techniques such as XPS, TEM and energy dispersive spectroscopy (EDS) shows that the films are made up of uniform spherical, crystalline SnO2 particles with the size in the range of 3-5 nm. Layer-by-layer (LbL) techniques can be exploited to stack graphene and SnO2 films alternately, in a desired sequence, forming a stacked composite structure. The composite structure is subjected to characterization by XPS, FE-SEM, TEM and EDS. The results show that the structure consists of a stack of predetermined thickness consisting of alternate layers of both the components. Such a structure is subjected to cyclic voltammetry (CV) studies. The results suggest LbL grown SnO2-GNS stacked composites exhibit better electrochemical performance in terms of specific capacitance and cycling ability which are primary requirements for the supercapacitor application. The coating techniques of few layer graphene nanosheets, SnO2 film and their stacked composite film are simple and inexpensive. A suitable explanation of the formation of both GNS and SnO2 films is discussed. The proposed methods extend the scope for production of high quality and defect free graphene nanosheets (GNS) and other components for forming LbL stacking of composite films.

Concurrent synthesis of SnO/SnO2 nanocomposites and their enhanced photocatalytic activity - Roy, Animesh; Arbuj, Sudhir; Waghadkar, Yogesh; Shinde, Manish; Umarji, Govind; Rane, Sunit; Patil, Kashinath; Gosavi, Suresh; Chauhan, Ratna (Journal of Solid State Electrochemistry, 2017)
The SnO/SnO2 nanocomposites were synthesized using semisolvothermal reaction technique. These nanocomposites were prepared using different combination of solvents viz., ethanol, water, and ethylene glycol at 180 A degrees C for 24 h. The synthesized nanocomposites were analyzed with various characterization techniques. Structural analysis indicates the formation of tetragonal phase of SnO2 for the sample prepared in ethanol, whereas for other solvent combinations, the mixture of SnO and SnO2 having tetragonal crystal structures were observed. The optical study shows enhanced absorbance in the visible region for all the prepared SnO/SnO2 nanocomposites. The observed band gap was found to be in the range of 3.0 to 3.25 eV. Microstructural determinations confirm the formation of nanostructures having spherical as well as rod-like morphology. The size of nanoparticles in ethanol-mediated solvent was found to be in the range of 5 to 7 nm. Thermogravimetric analysis indicate the weight gain around 1.3 wt% confirming the conversion of SnO to SnO2 material. The photocatalytic activity of synthesized nanocomposites was evaluated by following the aqueous methylene blue (MB) degradation. The sample prepared in ethylene glycol-mediated solvent showed highest photoactivity having apparent rate constant (K-app) 0.62 x 10(-2) min(-1).
Keywords: Dye-degradation; Nanocomposite; Photocatalysis; tin oxide

Detection of toxic metal ions Pb2+ in water using SiO2@Au core-shell nanostructures: A simple technique for water quality monitoring - Daware, Krishna; Kasture, Manasi; Kalubarme, Ramchandra; Shinde, Rakesh; Patil, Kashinath; Suzuki, Norihiro; Terashima, Chiaki; Gosavi, Suresh; Fujishim, Akira (Chemical Physics Letters, 2019)
The present paper demonstrates a development of simple, sensitive and selective optical probe for detection of Pb2+ ions in water using monodispersed silica-gold core-shell nanostructures (SiO2@Au NSs). Structural and elemental analysis confirms the phase purity of nanostructures. The SPR studies for SiO2 @Au NSs reveals, linear dynamic range for Pb2+ ions detection, in the concentration range of 100 ppb to 2 ppm, with detection limit of 100 ppb, which is 5 times higher than AuNPs. Cross sensitivity study confirm its selectivity towards Pb2+ ions over other metal ions. XPS analysis shows the interaction of Pb2+ ions with core-shell NPs.

Fluorescent carbon-dots thin film for fungal detection and bio-labeling applications - Gaikwad, Aarti; Joshi, Meenal; Patil, Kashinath; Sathaye, Shivaram; Rode, Chandrashekhar V. (ACS Applied Bio Materials, 2019)
The fluorescence properties of CDs, such as high quantum yield, tunability of emission color, and so on, make a strong potential material in various fields. These applications are mainly derived from in situ formation of surface functional groups, high chemical stability, biocompatibility, and easy interaction with substrates, etc. Mostly, the research applications of CDs concentrate on the labeling of biological species, drug delivery, and sensing in consequent biomedical applications. However, the detection of the fungal species/spores present in the environment by using CDs is rarely reported. Herein, we demonstrate CDs-based thin film as a sensor for detection of fungal spores from the environment. The procedure of detection is based on fluorescence, observed in the film of carbon dots deposited on quartz plates by using the Blodgett technique. It is observed that the CDs film shows quenching in the fluorescence intensity by the substrate, namely, fungal spores’ (Aspergillus niger, Penicillium chrysogenum, Alternaria alternata). The effective features of the present detector system are easy fabrication, low cost, high stability, and a green and economical procedure of synthesis. The process of detecting fungal spores even at low concentration from the atmosphere is relatively fast when compared to presently used methods. Finally, real-world feasibility of the sensor film is tested by its successful application for the determination of the presence fungal spores in the environment. Furthermore, CDs have been also successfully applied for the bio-labeling of Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) bacterial systems.

Synthesis of silver nanoparticles colloids in imidazolium halide ionic liquids and their antibacterial activities for gram-positive and gram-negative bacteria - Patil, Virendra; Mahajan, Swapnil; Kulkarni, Mohan; Patil, Kashinath; Rode, Chandrashekhar; Coronas, Alberto; Yi, Gi-Ra (Chemosphere, 2020)
Four 1-butyl-3-methylimidazolium halide ionic liquids were synthesized via metathesis and anion exchange reactions. Silver nanoparticles (AgNPs) colloids were synthesized in four ionic liquids in the pressurized reactor by reduction of silver nitrate with hydrogen gas, without adding solvents or stabilizing agents. Antibacterial activities of base ionic liquids and AgNPs colloids in ionic liquids were reviewed by well-diffusion method for gram-positive Bacillus cereus (NCIM-2155) and gram-negative Escherichia coli (NCIM-2931) bacteria. Antibacterial activities of ionic liquids and AgNPs colloids in ionic liquids were observed to be controlled by ionic liquids anions and AgNPs particle size. The 1 -butyl-3-methylimidazolium iodide ionic liquid exhibited higher antibacterial activities among the studied ionic liquids. Further, the presence of AgNPs in 1-butyl-3-methylimidazolium iodide, ionic liquid enhanced its antibacterial activity for Bacillus cereus and Escherichia coli bacteria. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Anion effect; antibacterial activity; Imidazolium halides; ionic liquids; silver nanoparticles